Enhanced Performance of a Microbial Fuel Cell Using Double Oxidant-Treated Carbon Felts - Bhavi Pandya; Latesh Chaudhari; Naresh R. Vaghela (Electrochem, 2025)
The aim of this study was to enhance and maintain bioelectricity generation from distillery spent wash using a microbial fuel cell (MFC). Electrode materials play a critical role in the generation of bioelectricity in MFCs. Utilizing double oxidant-treated carbon felts in MFC applications increased current density to 749.56 mA/m2 and increased peak power density to 125.23 mW/m2. Electrochemical impedance spectroscopy (EIS) analysis further verified the improved electrocatalytic activity observed in the oxidized carbon felt, consistent with the findings from cyclic voltammetry (CV) and polarization curves, thereby confirming the enhanced performance of the oxidized carbon felt electrode. Overall, the study highlights the significance of electrode morphology and surface modifications in influencing microbial adhesion, electron transport, and the overall efficiency of fuel cells using distillery spent wash as a substrate.